Some Commercially Important Indian Gum Exudates - Soni, P. L. (Indian Forester, 1995)
Gum exudates are important food additives besides being used in medicines, textiles, adhesives etc. Commercial applications of the gum depend upon its overall molecular structure and its properties. Exudate gums are facing stiff challenge from the modified starch or fermentation products. Food safety regulations have contributed to their restricted use in food industry. Six important Indian gums which have a place in the market are discussed and described in this paper.